الخط العربي كأحد الفنون التشكلية وجهود الإندونيسيين في تطويرها - محمد هادي مسروري (Universitas Negeri Malang, 2021)
That the calligraphy in its visual form compounded of interlocking letters lies the artistic aesthetic dimensions, which we call the implicit meaning of the visual texts, and it is able to stimulate the spiritual taste of sophisticated beauty. This article tries to emphasize that when calligraphy has addressed its textual and spiritual dimensions with the expansion of countries following the Islamic conquests, it is as if it is addressing minds and souls at the same time, and it won a wide turnout and intense passion on the part of those concerned with artistic taste. This is what happened in the Islamic countries of Egypt, the Gulf, Iran, Turkey, Pakistan, and other countries where the artist, who has a taste for high artistic beauty, lives. In Indonesia, those concerned with Islam and calligraphy, and whatever they lack the capacity to form Arabic letters with its standard patterns, made great efforts in dealing with Arabic calligraphy so that the two directions would follow: the direction of the organized calligraphy according to the known patterns of Arabic fonts, and the direction of calligraphy, or panting art. The owners of the second trend enter the world of creativity and innovation through their plastic paintings that name their owners in a mythical world between reality and fiction. This is thanks to a lot of stakeholders, whether individuals or governments.